Little Women - Alcott, Louisa May (Dover Publications Inc, 1997)
The Little Women has influenced and shaped people's lives for generations. In the background of American Civil War, the poignant enthusiasm of the March family is beautifully depicted. The novel is a reflection of the authoress' own childhood experiences in Boston.
Keywords: Fiction; Literary